2020
DOI: 10.21831/jpvo.v3i1.33555
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Hasil Belajar Siswa Melalui Model Pembelajaran Kooperatif Tipe Think Pair Share (Tps) Di SMK Negeri 1 Magelang

Abstract: This research aims to determine the increase in learning outcomes in the subject of Automotive Basic Technology class X Department of Automotive Engineering SMK Negeri 1 Magelang 2018/2019 Academic Year using the application of cooperative learning models Think Pair Share  (TPS) type. This research is a class action research. Data collection techniques used in this study used observation and tests. The steps undertaken in this study were begun with observations to find out the students' initial abilities in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Good learning outcomes require an appropriate learning model that will make students active both emotionally and socially (Putra Praditya & Haryana, 2020). Suprihatiningrum (2013) said that the learning model is a conceptual framework that can be described using systematic and varied learning procedures, which is useful so that students have a good learning experience so that students achieve the desired learning goals.…”
Section: Introductionmentioning
confidence: 99%
“…Good learning outcomes require an appropriate learning model that will make students active both emotionally and socially (Putra Praditya & Haryana, 2020). Suprihatiningrum (2013) said that the learning model is a conceptual framework that can be described using systematic and varied learning procedures, which is useful so that students have a good learning experience so that students achieve the desired learning goals.…”
Section: Introductionmentioning
confidence: 99%
“…Conducted in a class VIII-3 of SMP Negeri 1 Tapa with 25 students. The analysis showed that: (1) the validity, viewed from the learning tools developed and validated by the experts through validation sheets, obtaining a validation value of 3.50 and the category "valid"; (2) practicality, observed from the learning implementation obtained a percentage of 88.98% with category "very good" and observed from students' response on questionnaire with a percentage of 83.91% with category "good". It can be concluded that the quality of the Think-Pair-Share (TPS) Cooperative Model Learning Tools Integrated with Huyula aspect "valid and practical" to apply in lesson processing.…”
mentioning
confidence: 99%
“…Diselenggarakan dilkelaslVIII-3lSMPlNegeri 1 TAPAldenganl25 murid. Tahap analisis menerangkan (1) Kevalidan, diamati dari perangkat pembelajaran yang ldikembangkanldanldivalidasilolehlvalidatorlahlilmelaluillembaravalidasi mendapat skorasebesara3,50adengan kategori "valid"; (2) Kepraktisan, dilihat dari keterlaksanaan pembelajaran yang diperoleh dari pengamatan keterlaksanaan pembelajaran dengan presentasel88,98%ldenganlkategori "sangat baik" dan diamati dari respon peserta didik pada kuesioner dengan persentase 83,91% dengan kategori "baik". Sehingga disimpulkan bahwa kualitas Perangkat Pembelajaran Model Kooperatif Think Pair Share (TPS) terintegerasiiNilai -Nilai Huyula memenuhi aspek "valid dan praktis" untuk diaplikasikan di pelajaran.…”
unclassified